2014
DOI: 10.1104/pp.113.233387
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis CALLOSE DEFECTIVE MICROSPORE1 Gene Is Required for Male Fertility through Regulating Callose Metabolism during Microsporogenesis

Abstract: ORCID IDs: 0000-0002-3941-9955 (P.L.); 0000-0001-8717-4422 (H.M.).During angiosperm microsporogenesis, callose serves as a temporary wall to separate microsporocytes and newly formed microspores in the tetrad. Abnormal callose deposition and dissolution can lead to degeneration of developing microspores. However, genes and their regulation in callose metabolism during microsporogenesis still remain largely unclear. Here, we demonstrated that the Arabidopsis (Arabidopsis thaliana) CALLOSE DEFECTIVE MICROSPORE1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 51 publications
4
61
0
Order By: Relevance
“…First, AtC3H14 is a direct target of MYB46, a master switch for secondary wall biosynthesis, and was able to activate in vitro all of the eight secondary wall biosynthesis genes tested in a trans‐activation assay (Ko et al ., ; Kim et al ., ); Second, AtC3H14 and its homologs (e.g., AtC3H15 and PtC3H17 ) are predominantly expressed in secondary wall‐forming tissues (Figures , S1 and S2) and co‐expressed with MYB46 (Figure S3). Recently, it has been suggested that AtC3H15 may regulate callose metabolism during microsporogenesis (Lu et al ., ); Third, the transgenic plants overexpressing AtC3H14 ( 35S::AtC3H14 ) showed early and aberrant phloem fiber development both in the stems and roots (Figure ). Fourth, these phenotypes are consistently reproduced in the transgenic plants overexpressing its Arabidopsis ( 35S::AtC3H15 ) and poplar homolog ( 35S::PtC3H17 ) (Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…First, AtC3H14 is a direct target of MYB46, a master switch for secondary wall biosynthesis, and was able to activate in vitro all of the eight secondary wall biosynthesis genes tested in a trans‐activation assay (Ko et al ., ; Kim et al ., ); Second, AtC3H14 and its homologs (e.g., AtC3H15 and PtC3H17 ) are predominantly expressed in secondary wall‐forming tissues (Figures , S1 and S2) and co‐expressed with MYB46 (Figure S3). Recently, it has been suggested that AtC3H15 may regulate callose metabolism during microsporogenesis (Lu et al ., ); Third, the transgenic plants overexpressing AtC3H14 ( 35S::AtC3H14 ) showed early and aberrant phloem fiber development both in the stems and roots (Figure ). Fourth, these phenotypes are consistently reproduced in the transgenic plants overexpressing its Arabidopsis ( 35S::AtC3H15 ) and poplar homolog ( 35S::PtC3H17 ) (Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…CALLOSE DEFECTIVE MICROSPORE 1 (CDM1), acts on callose biosynthetic and degrading genes [90], while AtTTP (TRISTETRAPROLINE) forms a genetic pathway including AtTTPmiR160-ARF17-CalS5 [91]. Furthermore, AtbZIP34 was shown to modulate pollen wall development by targeting six genes associated with lipid metabolism and/or transport, including AtABCB9 [92].…”
Section: Coordinated Regulation Of Pollen Wall Developmentmentioning
confidence: 98%
“…After meiosis, the tapetum secretes b1,3 glucanase (callase), which breaks down the callose layer surrounding the tetrads and releasing the microspores into the locule (Lu et al 2014). The timing of callase secretion appears critical for pollen development (Bedinger 1992), with miss-expression causing sterility (Worrall et al 1992).…”
Section: Pollen Wall Formationmentioning
confidence: 99%